Land Compensation and Policy Enforcement in Vietnam: A Case Study in Danang - Tuan Nguyen Tran; Hegedűs Gábor (Real Estate Management and Valuation, 2022)
The land is a natural resource which is rich in diversity, and its value tends to increase over time. Therefore, compensation in cases when the State acquires land, is an issue of concern. Using data from 100 surveyed households and ten interviews (including 5 houesholds indirectly affected by land acquisition, 3 relevant experts, and 2 village headmen) in Da Nang, the article aims to answer two research questions: (1) assessment of landless households on land compensation policy, and (2) an assessment of outstanding issues in this policy in Vietnam. The results show that the local government has strictly followed the regulations and procedures of the State on land acquisition and compensation for economic development purposes under the 2013 Land Law. However, affected people feel dissatisfied with what they had received when they lost land. The first reason is the significant difference between the compensation prices households received and the market price, as determined by a real estate broker. Second, concerns about the future arise when a family’s means of production are acquired by the state. In addition, the policy also lacks support measures for households located in affected areas. These shortcomings lead to dissatisfaction among families.